Effect of hula hoop training on the cardiovascular Parameters in grade I obese subjects - SURYA KRISHNANUNNI; DR. VISHNU VARDHAN; DR. AASHIRWAD MAHAJAN (International Journal of Pharma and Bio Sciences, 2018)
Obesity is most commonly caused by a combination of excessive food intake and physical inactivity. The hula hoop has been practiced by people to be physically active while having fun. Hooping is a complex skill in which, a hoop in its spherical symmetry, is kept in steady oscillation parallel with the ground by means of oscillations of different parts of the body, in uncountable variations of creativity. The purpose of this study is to assess the potential of hula hoop training based on physically simulated play as physical activity that could have benefits on the cardiovascular parameters in adults with obesity. By purposive sampling method 30 subjects, male and female (19-25 years) with Grade I Obesity were selected and a four week trial with weighed hula hoops was done. Participants started with 2 minutes of hooping progressing to 25 minutes with breaks and by four weeks they were assessed pre and post by measuring their Heart rate manually, Blood pressure by mercury sphygmomanometer and Body mass index (BMI).This experimental study concluded that the heart rate and blood pressure were significantly decreased with Hula Hooping activity, and also helped in reducing the BMI very significantly in subjects with Grade I Obesity.